Engendering Macroeconomic Theory and Policy - Seguino, Stephanie (World Bank, Washington, DC, 2017)
Over the last 20 years, macroeconomists have increasingly given attention to the role of gender in the macroeconomy and the implications of macro-level policies for gender equality. This paper reviews the salient findings of that literature. Research shows that gender gaps in education, health, unpaid labor, employment, and wages affect the macroeconomy, influencing the rate of per capita GDP growth. The effects are transmitted via both the supply side of the economy, principally through labor productivity, and the demand side, through business spending, exports, saving, and the balance of payments. Theoretical perspectives influence which gender gaps are incorporated into models as well as how. For example, heterodox economists emphasize the demand and supply side in the short and long run, while neoclassical economists tend to focus on long-run supply-side effects. There is widespread agreement in the literature that greater gender equality in education and employment (proxied by labor force participation rates) stimulates long-run per capita growth. Improving women’s relative productivity through educational investments and facilitating their participation in paid labor serves several purposes. For example, assuming talent is equally distributed across men and women, a narrowing of gender gaps in education and employment contributes to higher average educational attainment and a more efficient allocation of labor. As educational attainment rises and women gain greater access to paid work, the opportunity cost of having additional children also rises, leading to a decline in fertility rates. Women’s bargaining power within the household rises at the same time. This increases their ability to allocate household spending in ways that benefit children, and as a result, economy-wide labor productivity growth. The weak link in this chain is that aggregate demand may be insufficient to absorb an increase in women’s relative labor supply. Demand-stimulating policies as well as other policy measures may be necessary to ensure women’s relative employment rate rises. Full employment policies can help to narrow the employment gap and well-targeted physical and social infrastructure investments have been found to promote women’s access to paid work. Finally, traditional monetary policy—that is, the use of interest rates to manage demand and by extension, inflation, has gender-related employment effects, and exchange rate policy also influences the gender wage gap. This area of policymaking has received much less attention than fiscal policy as a tool for promoting gender equality. The paper concludes with a discussion of areas for future research.